2018
DOI: 10.3892/etm.2018.6511
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin is valuable in the diagnosis of acute heart failure with renal insufficiency

Abstract: Acute heart failure (AHF) is a major public health issue due to its high incidence and poor prognosis; thus, efficient and timely diagnosis is critical for improving the prognosis and lowering the mortality rate. Amino-terminal pro-brain natriuretic peptide (NT-proBNP) is widely used in the diagnosis of AHF; however, its efficacy is controversial in diagnosing AHF with renal insufficiency. There were numerous studies reporting the association of adiponectin (ADPN) and heart diseases. Therefore, the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Recently, the association between NT-proBNP and adiponectin has been examined in adults with heart failure [5,30,31]. Some studies stated that the association of APN and heart failure vanished after adjusting for NT-proBNP [31], some revealed that high APN level was associated with increased risk of mortality, independent of plasma NT-proBNP [22], while Dai Z et al found an improved diagnostic value of conjunction of NT-proBNP and APN for heart failure [30]. While in our study, the diagnostic efficiency of adiponectin for detecting right ventricular dysfunction was not inferior or even probably better than NT-proBNP.…”
Section: Adiponectin and Nt-probnpmentioning
confidence: 99%
“…Recently, the association between NT-proBNP and adiponectin has been examined in adults with heart failure [5,30,31]. Some studies stated that the association of APN and heart failure vanished after adjusting for NT-proBNP [31], some revealed that high APN level was associated with increased risk of mortality, independent of plasma NT-proBNP [22], while Dai Z et al found an improved diagnostic value of conjunction of NT-proBNP and APN for heart failure [30]. While in our study, the diagnostic efficiency of adiponectin for detecting right ventricular dysfunction was not inferior or even probably better than NT-proBNP.…”
Section: Adiponectin and Nt-probnpmentioning
confidence: 99%
“…A meta-analysis by Bai et al suggested that elevated circulating APN levels might be associated with increased all-cause mortality and composite endpoints of death/readmission in patients with acute or chronic HF [ 123 ]. Dai et al demonstrated in clinical trials that APN is a valuable biomarker for acute HF, especially in patients with impaired renal function [ 124 ]. In addition to its application in HF clinical diagnosis, APN can be used for HF prognosis.…”
Section: Role Of Apn In Cardiovascular Disease and Related Advancesmentioning
confidence: 99%
“…[11,[119][120][121] Heart failure Biomarker for diagnosis and prognosis. [123][124][125] A key signal for the role of APN in CVD is AMPK, which plays a key role in regulating anabolic pathways related to energy expenditure by responding to changes in cellular energy status and ATP production/consumption [130], mediating glucose and lipid metabolism, mitochondrial biogenesis, inflammation, oxidative stress, cell proliferation and apoptosis, and cell hypertrophy. AMPK signaling pathway networks should be explored in future studies.…”
Section: Problems and Prospectsmentioning
confidence: 99%
“…The plasma concentration, stability, and diagnostic value of Nt-proANP and Nt-proBNP are higher in patients with chronic HF [ 22 , 23 ]. Studies have shown that the combined determination of adiponectin and NT-proBNP is more accurate than that of NT-proBNP alone [ 24 ]. Other diagnostic biomarkers, such as miR-302b-3p [ 25 ], Soluble ST2 [ 26 ], and Gal-3 [ 27 ], have recently been identified.…”
Section: Introductionmentioning
confidence: 99%